Senigallia historic town walls: materials and stability analyses - Busdraghi, Paolo; Veneri, Francesco; Iampieri, Valentina (Italian journal of engineering geology and environment, 2017)
<span data-sheets-value=""1":2,"2":"This work analyses the characteristics and state of preservation of the historical perimeter walls of the town of Senigallia (Ancona Province, Italy) and faces the problems tied to its degradation. This situation, in conjunction with incautious urban planning, has caused the loss of a sense of unity of the work, now absorbed and scattered in the current urban fabric; this renders its proper fruition difficult, arriving up to today’s situation in which the risk of being structurally compromised has arisen. This study presents innovative elements in the field of restoration work. The wall is analysed as if it were a geological body, especially the mortar characteristics which are its primary structural weakness; the analyses range from mineralogical – petrographic to physical-technical and were carried out both in situ and at the laboratory, with an evaluation of the foundation soil. The goal is the reconstruction of the current state of the Senigallia historic walls and, in particular, to bring out its technical, structural and physical characteristics of great architectural-historical value, in addition to its interaction with the geological substrate. This was carried out in order to identify the best restoration and preservation techniques so as to elaborate a peculiar Operations and Maintenance Manual for its constituent elements, bearing in mind the seismic properties of the area."" data-sheets-userformat=""2":15233,"3":"1":0,"10":1,"11":3,"12":0,"14":"1":2,"2":0,"15":"Arial","16":8">This work analyses the characteristics and state of preservation of the historical perimeter walls of the town of Senigallia (Ancona Province, Italy) and faces the problems tied to its degradation. This situation, in conjunction with incautious urban planning, has caused the loss of a sense of unity of the work, now absorbed and scattered in the current urban fabric; this renders its proper fruition difficult, arriving up to today’s situation in which the risk of being structurally compromised has arisen. This study presents innovative elements in the field of restoration work. The wall is analysed as if it were a geological body, especially the mortar characteristics which are its primary structural weakness; the analyses range from mineralogical – petrographic to physical-technical and were carried out both in situ and at the laboratory, with an evaluation of the foundation soil. The goal is the reconstruction of the current state of the Senigallia historic walls and, in particular, to bring out its technical, structural and physical characteristics of great architectural-historical value, in addition to its interaction with the geological substrate. This was carried out in order to identify the best restoration and preservation techniques so as to elaborate a peculiar Operations and Maintenance Manual for its constituent elements, bearing in mind the seismic properties of the area.